INTER-POPULATION COMPARISONS AND THE IMPORTANCE IN INFECTIOUS DISEASES OF THE IRF7, TBK1, IFNAR1, IFNAR2 AND TLR3 GENE VARIANTS IN TURKISH INDIVIDUALS - Aslı Karacan; Güven Toksoy; Zehra Oya Uyguner; Birsen Karaman; Seher Başaran; Ayşe Evrim Bayrak (İstanbul Tıp Fakültesi Dergisi)
Objective: In the research conducted during the pandemic period, it has been determined that IRF7, TBK1, IFNAR1, IFNAR2, and TLR3 immunity genes play an important role in the predisposition to SARS-CoV-2 infection. However, there is no information about variants of these genes in the Turkish population. The aim of this study was to determine the variants specific to the our study’s population in these genes that predispose to infections and to compare them with other populations. Materials and Methods: The variants in the exonic and flanking intronic regions of these five genes were analysed in in-house whole-exome sequencing data of 139 unrelated non-anonymous individuals. The allele frequencies of variants were compared with other population datasets. The DysGeNet database was used to determine human diseases associated with these genes. Results: In our population, gene variants were detected including 28 in IRF7, 16 in TBK1, 18 in IFNAR1, 19 in IFNAR2, and 9 in TLR3. The allele frequencies of variants were compared with other populations. Of these variants, 9 were determined to be novel, previously unreported variants. It was shown that these genes are mainly involved in cancer and infectious diseases, especially viral infections according to the DisGeNET database. Conclusion: The determination of immunity gene variants specific to our population and the variability of allele frequencies among populations suggest that it may cause differences in immune response, especially to SARS-CoV-2 infection. In this study, preliminary information was obtained for studies that will investigate the relationship between the clinical manifestations of infectious diseases and immunity gene variants.